Roberto Marín Guzmán. Popular Dimensions of the ’Abbasid Revolution. A Case Study of Medieval Social History. Cambridge y Massachusetts: Fullbriht-Laspau, 1990. XII + 160 pp. (glosario, bibliografía e índice). - Nájera, David (Estudios de Asia y África, 1993)
-